2015
DOI: 10.1128/jcm.02413-14
|View full text |Cite
|
Sign up to set email alerts
|

First Experience of a Multicenter External Quality Assessment of Molecular 16S rRNA Gene Detection in Bone and Joint Infections

Abstract: The objective of this study was to assess the performance of seven French laboratories for 16S rRNA gene detection by real-time PCR in the diagnosis of bone and joint infection (BJI) to validate a large multicenter study. External quality control (QC) was required owing to the differences in extraction procedures and the molecular equipment used in the different laboratories. Three proficiency sets were organized, including four bacterial DNA extracts and four bead mill-pretreated osteoarticular specimens. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The results obtained with our technology showed that in only 10% of the samples (34 out of 333) no bacteria were detected, and in the remaining 90%, 1 to 5 bacteria could be detected per sample, with a peak of 2 bacteria per sample in 40% of the total samples ( Figure 1 A). This result is in agreement with other molecular biology techniques that often detect more than one bacterium in bone and joint infections [ 13 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 91%
“…The results obtained with our technology showed that in only 10% of the samples (34 out of 333) no bacteria were detected, and in the remaining 90%, 1 to 5 bacteria could be detected per sample, with a peak of 2 bacteria per sample in 40% of the total samples ( Figure 1 A). This result is in agreement with other molecular biology techniques that often detect more than one bacterium in bone and joint infections [ 13 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 91%
“…Custom-made methodologies, based mainly in 16S rDNA amplification and sequencing, have high sensitivity and specificity, 38 , 39 and even high reproducibility is described in some reports. 40 , 41 These later studies are extremely important, because a well-known claimed limitation of this technology is the lack of reproducibility. In the study by Plouzeau et al 40 , 41 a control was submitted to different laboratories that have previously published the multicentre study.…”
Section: Biomolecular Techniquesmentioning
confidence: 99%
“… 40 , 41 These later studies are extremely important, because a well-known claimed limitation of this technology is the lack of reproducibility. In the study by Plouzeau et al 40 , 41 a control was submitted to different laboratories that have previously published the multicentre study. 40 , 41 The results of reproducibility showed that, in well-trained experienced laboratories, this approach could be very useful and reproducible.…”
Section: Biomolecular Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our West French network organization (Centre de Référence des Infections Ostéoarticulaires du Grand Ouest [CRIOGO]) for the multidisciplinary diagnosis and treatment of bone and joint infections in seven referral centers allowed us to carry out the first prospective multicenter study related to the molecular and histopathological diagnosis of PJI. The contribution of broad-range PCR to the diagnosis was recently published (17,18).…”
mentioning
confidence: 99%